Stable co-expression of [a]-amylase and glucoamylase genes transformed into Saccharomyces cerevisiae - Steyn, Andries Johannes Christoffel,1963- (Stellenbosch : Stellenbosch University, 2012)
[a] in title replaces symbol for alpha.